Exploring Figurative Language in Weyes Blood's Song “A Lot’s Gonna Change” - Maulidya, Alya; Adiyat, Zuna El; Haenzel, Bryan Fillemon; Fahlan, Syam Indra (Universitas Pamulang, 2026)
This study focuses on identifying the types of figurative language used throughout Weyes Blood’s “A Lot’s Gonna Change” and understanding how these expressions shape the emotional meaning of the song. Figurative language plays an important role in songwriting because it helps artists express feelings that are often too personal or too abstract to describe in a literal way. Based on the analysis, five types of figurative language were found in the lyrics. Such as metaphor 1 (20%), personification 1 (20%), hyperbole 1 (20%), symbolism 1 (20%), and irony 1 (20%). One notable use of personification shows how the song gives life to abstract ideas, allowing listeners to connect emotionally with the message. This study uses a qualitative descriptive approach, examining the lyrics through close reading to identify figurative expressions and interpret their contextual meanings. Each figure of speech contributes to the song’s themes of nostalgia, personal growth, and the emotional weight of change. Instead of explaining her feelings directly, Weyes Blood uses imagery and subtle comparisons to guide listeners through the shift between past innocence and present maturity. Through these devices, the song transforms personal memories into something universal. Ultimately, “A Lot’s Gonna Change” delivers a gentle reminder about embracing life’s transitions while staying grounded in who you truly are.